Graphical evaluation of robust parameter designs based on extended scaled prediction variance and extended spherical average prediction variance - Oh, Jin H.; Park, Sung H.; Kwon, Soon S. (Communications in Statistics - Theory and Methods, 2018)
For any response surface design, there are locations in the design region where responses are estimated well and locations where estimation is relatively poor. Consequently, graphical evaluation—such as variance dispersion graphs and the fraction of design space—is used as an alternative to a single-valued criterion. Such plots are used to investigate and compare the prediction capabilities of certain response surface designs currently available to the researcher. In this article, we propose the extended scaled prediction variance and extended spherical average prediction variance as prediction methods. We also illustrate how graphical methods can be employed to evaluate robust parameter designs.
Keywords: Fraction of design spaces; Graphical evaluation; Prediction Variance; Robust parameter design; Scaled Prediction Variance; Variance dispersion graph; Extended scaled prediction variance; Extended spherical average prediction variance; Fraction of design space; Graphical evaluation; Robust parameter designs; Variance dispersion graphs